ChemInform Abstract: Facile Synthesis of α‐Methylidene‐γ‐butyrolactones: Intramolecular Rauhut—Currier Reaction Promoted by Chiral Acid—Base Organocatalysts. Issue 22 (13th May 2013) - Takizawa, Shinobu; Nguyen, Tue Minh‐Nhat; Grossmann, Andre; Suzuki, Michitaka; Enders, Dieter; Sasai, Hiroaki
Abstract Highly functionalized α‐methylidene‐γ‐butyrolactones are formed enantioselectively from prochiral dienone enolates in the presence of chiral organocatalysts (CHOC).